EVALUATE THE RELATIONSHIP BETWEEN EOSINOPHILS AND COVID-19 PATIENTS. - Salam Hammad Husien; MOHANED ADEL JAYAN; MOHAMMED MYASAR DAWAD (Scholar Express Journals, 2022)
This study aims to evaluate and know the relationship between eosinophilia and COVID-19 patients Patients were collected from different hospitals in Iraq, where 50 patients were collected and divided into two groups with eosinophilia that included 30 patients, and without eosinophilia, 20 patients After obtaining the necessary approvals from the Ethics Committee to carry out this study, it will study and analyze the demographic data of patients for a period of one full year from 5-5-2020 to 6-9-2021, and we found A positive relationship was found between eosinophilia in Covid-19 patients
Keywords: Eosinophils; Covid-19; Cells; Comorbidities